2022
DOI: 10.3389/fendo.2022.847760
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Shared Gene Signatures and Biological Mechanism in Type 2 Diabetes and Pancreatic Cancer

Abstract: BackgroundThe relationship between pancreatic cancer (PC) and type 2 diabetes mellitus (T2DM) has long been widely recognized, but the interaction mechanisms are still unknown. This study was aimed to investigate the shared gene signatures and molecular processes between PC and T2DM.MethodsThe Gene Expression Omnibus (GEO) database was used to retrieve the RNA sequence and patient information of PC and T2DM. Weighted gene co-expression network analysis (WGCNA) was performed to discover a co-expression network … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 55 publications
(50 reference statements)
0
16
0
Order By: Relevance
“…Previous studies identified shared gene signatures and biological mechanisms in type 2 diabetes and pancreatic cancer by utilizing the WGCNA method ( Hu et al, 2022 ). To further explore the relationship between gene expression and abundance of CAFs, we performed the WGCNA according to the expression profiles of all genes (17,003 genes) by utilizing the R package WGCNA ( Langfelder and Horvath, 2008 ) and next identified the remarkable gene modules positively correlated with the fraction of CAFs.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies identified shared gene signatures and biological mechanisms in type 2 diabetes and pancreatic cancer by utilizing the WGCNA method ( Hu et al, 2022 ). To further explore the relationship between gene expression and abundance of CAFs, we performed the WGCNA according to the expression profiles of all genes (17,003 genes) by utilizing the R package WGCNA ( Langfelder and Horvath, 2008 ) and next identified the remarkable gene modules positively correlated with the fraction of CAFs.…”
Section: Methodsmentioning
confidence: 99%
“…As previous studies have done ( Hu et al, 2022 ; Jiang et al, 2022 ), differentially expressed genes (DEGs) were screened in GSE48452 and GSE63067 in a batch-calibrated screening set. DEGs between NAFLD samples and normal samples were screened using the limma program package, with P. adj.…”
Section: Methodsmentioning
confidence: 99%
“…To ensure the high positive correlation between the selected module and the corresponding disease, we selected the two modules with the highest positive correlation coefficient and the highest significance in SLE (Meblue and Metan), Meblack and Mebrown modules were selected in DLBCL using the same method 15,16 . In the SLE and DLBCL highly positivity related modules, there were 47 overlapping genes, which were defined as common genes (CGs) (Supplementary Figure 2).…”
Section: Common Gene Signatures In Sle and Dlbclmentioning
confidence: 99%